Driving under the influence of drugs or alcohol: Predicting the intentions of young drivers. (17th February 2021) - Vankov, Daniel; Schroeter, Ronald
Abstract: Objectives: Driving under the influence (DUI) of drugs or alcohol impairs driving performance and, as a result, increases the risk of crashes. The risk of DUI is five-fold higher for young drivers (aged 18-25 years), but little is known about what determines their DUI intentions. This study applied an extended model of the Theory of Planned Behavior (TPB) to address the research question of what factors might influence young drivers' future intentions to DUI. Methods: This study used a survey obtaining data from 329 young drivers (Mage = 20.92 years, SD  = 2.16) in Australia. Beyond the standard TPB measures of attitudes, subjective norms and perceived behavioral control (PBC), the current study included demographic variables and additional predictors (i.e., moral norm, peers' norm, perceived risk, impulsivity and past DUI behavior). Results: A vast majority of the participants (85.1%) selected the maximum (9, never), meaning that they had no intention to DUI in the future. Overall, a stepwise multilevel logistic regression analysis (Step 1: demographics, Step 2: TPB measures, and Step 3: additional predictors) explained between 30.1% and 52.9% of the variance in DUI intentions. It showed past DUI behavior as the strongest predictor of DUI intention, followed by instrumental attitude and descriptive norms. Conclusions: This study explored an extended TPB model to understand young drivers' DUI intentions better. With this new knowledge of understanding the factors that influence DUI, researchers and practitioners can create interventions and strategies that are better tailored to the population of young drivers at higher risk.